Winter recovery in Sweden of a Dutch Blackcap Sylvia atricapilla - Tengholm, Anders; Tengholm, Johan; Ekblom, Robert (Ornis Svecica, 2018)
In February 2018, a European Blackcap Sylvia atricapilla that had been ringed as a yearling in the Netherlands in the previous autumn was trapped in Uppsala, Sweden (59.8°N). Winter records of Blackcaps are not uncommon in Sweden but this is the first recovery of a bird with documented southern origin. The finding is in line with reports that a relatively high proportion of ringed Blackcaps is recovered in the same autumn north of the ringing site, and that the fraction of short-winged Blackcaps of presumed southern origin increases late in the season at Swedish bird observatories. Although the present record provides evidence that Blackcaps wintering in Sweden may originate from Continental Europe, it appears unlikely that the Blackcap will be able to evolve a new migration pattern, similar to the population of Continental Blackcaps wintering in Britain, because few Blackcaps seem to survive the Swedish winter.